Prospective memory in patients with relapsing remitting Multiple Sclerosis - Cores, Evangelina Valeria (2017)
Prospective Memory (PM) is a set of cognitive abilities that allow us to remember to perform planned actions or delayed intentions. It requires the recall of the content of the planned task in the form of an intention to be able to execute it at the 4 appropriate moment. Previous studies have yielded conflicting results as some show that MS patients have difficulty in remembering the content of intentions and others in the process of self-initiation of delayed intentions. Moreover, the relationship between PM and clinical variables also remains unclear. The aim of this study is to investigate PM in Relapsing-Remitting Multiple Sclerosis (RRMS) with two experimental tests that evaluate different aspects of the MP. Another aim of the current study was to analyse the relationship between PM and demographic variables and clinical variables. Methods: 36 outpatients with a diagnosis of RRMS attending to two centers specialized in multiple sclerosis clinics, were recruited. Thirty five healthy volunteers formed the contrast group (CG), matched for age, gender and education with the MS patients. A neuropsychological test battery that included two techniques for measuring PM was administered. The Cóndor test consists of reading a text whilst simultaneously executing many actions. In the Multitask Prospective Memory (MTPM), the participant must remember to initiate a complex intention, which was previously planned. The test yields formation scores of the intention, initiation, plan retention capacity and finally two execution scores. A depression scale (Beck Depression Inventory, BDI-II) was administered and physical disability was revealed using the Expanded Disability Status Scale. Results: In the RRMS group, the majority of patients (80.6%) had none or minimal signs of depression according to BDI-II classification criteria. Seventy five % of patients were in full- or half-time employment, 13.9% were unemployed or in occasional employment and 11.1% were house wives or retired on grounds of age. With respect to cognitive performance 47.2% of MS patients presented cognitive impairment. RRMS patients and the CG did not differ significantly on age and years of formal education. Groups showed no significant differences in distribution of Gender. Patients scored significantly lower than the CG on the Cóndor?s total score, p = 5 .007, d = 0.7. On the MTPM, the CG obtained significantly more points for intention formation than patients, p = .027, d = 0.5. Sixty-three percent of patients versus 88.5% of the CG self-initiated the intention, p = .014. Patients who obtained a higher score on Formation, self-initiated more often, p = .012. Education, disease progression and depression measure with the Beck Depression Inventory, significantly and mildly correlate with the Cóndor and the MTPM. Physical disability was only associated with the intention planning phase of MTPM. Conclusion: PM appears to be impaired in patients with RRMS. A deficit was found in planning and self-initiation of planned actions. Self-initiation was influenced by planning quality. Education, disease progression and depression were shown to influence recall and execution of future intentions. Physical disability was only associated with the intention planning phase. Some previous studies have not found a significant relationship between physical disability and cognitive measures. This study suggests that PM can be affected in patients with a low level of physical impairment. Results highlight the need for objective assessment of PM in RRMS patients to be able to detect any disorder in the initial stages of the disease and start appropriate rehabilitation. Amongst the limitations of this study, the observational, non-blind design must be acknowledged, as well as the small sample size. Also, the instruments used to assess PM are relatively new and studies of their psychometric properties are lacking. Nevertheless, the use of an instrument like El Cóndor is notable, given that it was developed for local population.